Assessing the Relevance of Statistics and Crime Analysis Courses for Working Crime Analysts. Issue 2 (3rd April 2017) - Kringen, Jonathan Allen; Sedelmaier, Christopher M.; Elink-Schuurman-Laura, Kristin D.
Abstract : Crime analysts study criminal activity and police function to improve performance. Analysts inform operations, aid resource allocation, and evaluate programs. These tasks require high levels of statistical literacy. Given that most analysts are college-educated civilians, college coursework in statistics and/or crime analysis may represent the foundational knowledgebase within the profession. However, little research has attempted to determine if coursework teaches the skills needed by analysts. Underlying this issue is a limited understanding about what technical skills crime analysts regularly use. Analyzing parallel surveys of 98 criminal justice educators and 146 crime analysts, this study compares the skills taught in undergraduate-level statistics and crime analysis courses to those used by analysts. Comparisons are made between perceptions of the value of coursework. Results indicate discrepancies between the orientation of coursework and the needs of analysts which underscore differences in the perceived relevance of statistics education. Recommendations are discussed.